1997
DOI: 10.1094/mpmi.1997.10.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression of the Cutinase A Gene of Botrytis cinerea

Abstract: Cutinase of Botrytis cinerea has been suggested to play an important role in penetration of host tissues. A protein fraction with cutin hydrolyzing activity was purified from culture filtrates of B. cinerea induced for cutinase activity. An 18-kDa protein in this fraction was identified as cutinase and the corresponding gene cutA was cloned. The gene is present in a single copy in the genome of B. cinerea strain SAS56 and its predicted amino acid sequence shows significant homology (31 to 35% identity) to othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 25 publications
1
48
0
1
Order By: Relevance
“…cutA has previously been shown to be induced in B. cinerea mycelium in the presence of cutin monomers and repressed by glucose (48,61,62). We found that cutA and cutB were induced during germination with different kinetics (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…cutA has previously been shown to be induced in B. cinerea mycelium in the presence of cutin monomers and repressed by glucose (48,61,62). We found that cutA and cutB were induced during germination with different kinetics (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…This includes the ability of the fungus to penetrate the leaf surface, relevant to this study as plants were not wounded prior to inoculation, and possibly the extent of plant defense activation by attempted fungal penetration of the leaf surface. However, the loss of penetration-related enzymes, such as cutinase, or the ability to form penetration structures, such as appressoria, have not impaired B. cinerea pathogenicity in experimental settings van Kan et al 1997;Gourgues et al 2004). Loci associated with A. thaliana ''penetration'' mutants, whose defects allow inappropriate penetration of A. thaliana leaves by non-Arabidopsis pathogens, are not colocalized with B. cinerea early lesion QTL detected in this study (Collins et al 2003;Assaad et al 2004;Stein et al 2006).…”
Section: Discussionmentioning
confidence: 51%
“…Recent results obtained with cutinase gene-disrupted mutants of Magnaporte grisea [5], F. solani [6^8], Alternaria brassicicola [9] and Botrytis cinerea [10,11] have not con¢rmed this concept of a dual cutinase function. Although virulence penalties reported for a gene-disrupted mutant of F. solani remain controversial [7,12], the disruption of cutinase genes strongly expressed during saprophytic growth of the pathogens on cutin had no apparent e¡ect on the pathogenicity of respective mutants.…”
Section: Introductionmentioning
confidence: 99%